Comparative analysis of circulating tumor DNA stability In K3EDTA, Streck, and CellSave blood collection tubes - Kang, Qing; Henry, N. Lynn; Paoletti, Costanza; Jiang, Hui; Vats, Pankaj; Chinnaiyan, Arul M.; Hayes, Daniel F.; Merajver, Sofia D.; Rae, James M.; Tewari, Muneesh (Clinical biochemistry, 2016)
Optimal conditions for blood collection for circulating tumor DNA (ctDNA) are still being developed. Although both Streck and EDTA tubes are commonly used, their ability to stabilize ctDNA as a function of time and temperature post-collection has not been thoroughly studied. Additionally, the potential utility of CellSave tubes (commonly used for circulating tumor cell) for ctDNA measurements has not been studied. Blood was collected into Streck, EDTA, and CellSave tubes from ten patients with metastatic breast cancer enrolled in the MI-ONCOSEQ tumor sequencing program at the University of Michigan and kept either on ice or at room temperature until plasma isolation. Plasma was processed after 2, 6, and 48h post-collection. We used droplet digital PCR (ddPCR) to quantify plasma ctDNA and wild-type DNA for six patients who had tumor tissue mutations represented in commercially available ddPCR assays. ctDNA abundance was similar and stable for up to 6h in all tube types, and there was no effect of storage temperature on the yield for Streck and EDTA tubes. After 48h, however, one out of four patients with detectable ctDNA showed a ~50% decline in ctDNA in the EDTA tube, and three out of six patients showed a 2–3-fold increase in wild-type DNA in the EDTA tube. Streck, EDTA, and CellSave tubes showed similar performance in preserving ctDNA for up to 6h before plasma isolation. Streck and CellSave tubes more consistently stabilized ctDNA and wild-type DNA at 48h than EDTA tubes. •All three tubes are effective in stabilizing ctDNA and genomic DNA if plasma is isolated within 6hours.•If plasma processing is delayed for 48hours, EDTA tubes can show an increase in WT DNA.•CellSave tubes can show a modest but statistically significant decline in WT DNA in some patients.•Streck tubes provide extended stability if kept at room temperature.